Apollo, Hercules and Chrysas in Cicero’s ‘De Signis’ (Verr. 2, 4, 93‑96) - Beltrão, Claudia (Romanitas - Revista de Estudos Grecolatinos, 2019)
Cicero’s De signis, the fourth speech of the second actio of the Verrines, is an oustanding source for the study of divine statues and the modes of religious perception, knowledge and practices on late republican Rome. Cicero’s speech is plenty of informations on these statues, its places, on gestures and emotions related to them, in dealing with religious affectivity. In a brief section of the De signis, we could see the materialisation of the conflict between the (bad) propraetor and the (good) allied people in the divine statues of Apollo, Hercules and Chrysas. Cicero praises the violent responses of local populations against a violent and unworthy Roman magistrate, as Cicero constructs the figure of Verres. The orator does not just reflect concepts and ideas about the deities but, based on shared beliefs, momentary fears and hopes Cicero actually creates them for his audience.
Keywords: Divine statues; Verrines; Cicero; Roman religion